ISOTOPIC INFERENCES ON THE CHEMICAL STRUCTURE OF THE MANTLE - Carlson R.W. (My University, 1995)
Variations in the isotopic composition of rocks derived from the upper mantle can be used to infer the chemical history and structure of the Earth's interior. The most prominent material in the upper mantle is the source of mid-ocean ridge basalts (MORB). The MORB source is characterized by a general depletion in incompatible elements caused by the extraction of the continental crust from the mantle. At least three other isotopically distinct components are recognized in the suboceanic mantle. All three could be generated by the recycling of near surface materials (oceanic crust, pelagic sediments, continental lithospheric mantle) into the mantle by subduction. Therefore, the isotope data do not require a compositionally layered mantle, but neither do they deny the existence of such layering. Correlations between the volumetric output of plume volcanism with the reversal frequency of the Earth's magnetic field, and between the geographic distribution of isotopic variability in oceanic volcanism with seismic tomography suggest input of deep mantle material to surface volcanism in the form of deep mantle plumes. Volcanism on the continents shows a much wider range in isotopic composition than does oceanic volcanism. The extreme isotopic compositions observed for some continental magmas and mantle xenoliths indicate long-term (up to 3.3 Gyr) preservation of compositionally distinct material in thick (>200 km) sections of continental lithospheric mantle.